Global Trend Analysis and Projections on Natural Resource Economics in Islam - Dinny Rahmayani Zebua; Mandasari (Journal of Global Islamic Economic Studies, 2024)
The global environmental crisis, the overexploitation of natural resources (SDA), and the inequality of wealth distribution are major challenges in contemporary economic governance. Various natural resource management models sourced from the capitalistic paradigm are considered not fully able to answer the issues of sustainability and justice. Islam as a holistic value system offers natural resource economics principles based on justice, responsibility, and ecological balance. This research aims to analyze global trends and projections on natural resource management and examine how Islamic economic principles can be integrated in dealing with these dynamics. Through a qualitative approach with a literature study method, this study explores classical and contemporary literature related to natural resource economics in Islam, global trends such as green economy and ESG, and challenges faced by Muslim countries in natural resource governance. The results of the study show that Islamic values such as amanah, milkiyyah 'ammah, israf prohibition, and sharia maqashid are very relevant to the direction of global policies that prioritize sustainability and social justice. Islam not only provides normative solutions, but also provides a regulatory and operational framework for sustainable natural resource management. The novelty of this study lies in the synthesis between Islamic economic principles and global trends in natural resource management which have rarely been comprehensively discussed in previous academic studies. This research also confirms that Islamic economics has great potential to become a strategic alternative in global natural resource governance through the integration of spiritual values, environmental ethics, and applicable social responsibility. These findings are expected to enrich the scientific discourse and become the basis for more equitable and sustainable policy formulation, especially in countries with Muslim majority populations.